Utilizing Sensory Marketing and Brand Experience: The Case of Luxury Watchmaking - Chandra, Axton Trixie; Balqiah, Tengku Ezni (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
This research examines the impact of sensory marketing cues and brand experience on emotional attachment, customer commitment, and brand loyalty in the luxury wristwatch industry. The study, conducted with 323 Indonesian consumers who purchased luxury wristwatches, reveals significant associations among sensory marketing cues, brand experience, emotional attachment, customer commitment, and brand loyalty. However, the effect of store image was found to be insignificant in moderating the connections between sensory marketing cues, brand experience, and emotional attachment. These findings highlight the importance of sensory marketing cues and brand experience in fostering emotional attachment and customer commitment, ultimately leading to brand loyalty. The results provide valuable insights for luxury wristwatch manufacturers and distributors in Indonesia to enhance customer loyalty through effective marketing strategies and optimized retail experiences. However, caution must be exercised in generalizing these implications to other countries or industries. Additionally, this study contributes to the literature on brand loyalty, particularly in the luxury wristwatch industry, by addressing the challenges posed by emerging substitutes such as advanced smartwatches and offering guidance on maintaining brand loyalty amidst increasing competition.